Pelatihan Penanganan Perilaku Negatif Remaja Autistik pada Masa Pubertas bagi Orang Tua dan Guru SMPLB di SLB Negeri 1 Lombok Barat - Wiwiek Zainar Sri Utami; Lu’luin Najwa; Menik Aryani; Eneng Garnika (Jurnal Pengabdian UNDIKMA, 2020)
The training in handling autistic adolescent negative behaviour at the puberty stages for SMPLB teachers at SLB Negeri 1 Lombok Barat. It was held on the hall of SMPLB 1 Lombok barat involving their parents and teachers. This training aims to provide a right skills and knowledge in handling autistic adolescent negative behaviour in their puberty stages. The method of this training included the theory explanation, advantages, application, demonstration, and direct practice between the participants to handling negative behaviour. The evaluation of this training found that there was a high enthusiasm from parents that attend the training completely. The assessment of practical assignments illustrates the success of the presented material. It also look closely to participant performance and participation. Furthermore, data meaningfulness was collected by the team from participants at the end of the training. Overall, this training program probably should always be held to enhance parents' and teachers' skills and knowledge in handling autistic adolescent negative behavior.